Functional genomic analysis of epithelioid sarcoma reveals distinct proximal and distal subtype biology - Rasmussen, Samuel; Jin, Jia Xiang; Bickford, Lissett R.; Woods, Andrew D.; Sahm, Felix; Crawford, Kenneth A.; Nagamori, Kiyo; Goto, Hiroaki; Torres, Keila E.; Sidoni, Angelo; Rudzinski, Erin R.; Thway, Khin; et al. (Clinical and translational medicine, 2022)
Background Metastatic epithelioid sarcoma (EPS) remains a largely unmet clinical need in children, adolescents and young adults despite the advent of EZH2 inhibitor tazemetostat. Methods In order to realise consistently effective drug therapies, a functional genomics approach was used to identify key signalling pathway vulnerabilities in a spectrum of EPS patient samples. EPS biopsies/surgical resections and cell lines were studied by next-generation DNA exome and RNA deep sequencing, then EPS cell cultures were tested against a panel of chemical probes to discover signalling pathway targets with the most significant contributions to EPS tumour cell maintenance. Results Other biologically inspired functional interrogations of EPS cultures using gene knockdown or chemical probes demonstrated only limited to modest efficacy in vitro. However, our molecular studies uncovered distinguishing features (including retained dysfunctional SMARCB1 expression and elevated GLI3, FYN and CXCL12 expression) of distal, paediatric/young adult-associated EPS versus proximal, adult-associated EPS. Conclusions Overall results highlight the complexity of the disease and a limited chemical space for therapeutic advancement. However, subtle differences between the two EPS subtypes highlight the biological disparities between younger and older EPS patients and emphasise the need to approach the two subtypes as molecularly and clinically distinct diseases.
Gesehen am 22.02.2023